2021
DOI: 10.1093/hsw/hlab042
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review of Relational Autonomy in Dialysis Decision Making

Abstract: Nephrology interdisciplinary guidelines, professional codes of ethics, principle-based ethical standards, and literature promote patient autonomy and self-determination through shared decision making as ethical practice. Healthcare professionals are accountable for practice that is mindful of the impact of cultural diversity and community on the values and beliefs of the patient, an important part of shared decision making (SDM). Despite previous research regarding dialysis decision making, relational autonomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Relational autonomy, on the other hand, acknowledges the influence of context (e.g., relationships, roles, spirituality, daily routines) and structure (e.g., social norms, sociopolitical, economic) on decision-making (Oshana, 2006). Rather than treatment decision conversations shaped from a perspective of individual autonomy and regulatory adherence (e.g., annual comprehensive patient assessments), the integrated care provider, patient, and DP should consider treatment decisions relationally and therefore engage in ongoing dialogue with the goal of the mutual understanding of experience, motivations, needs, and conditions (Phillips, 2007; Sledge et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relational autonomy, on the other hand, acknowledges the influence of context (e.g., relationships, roles, spirituality, daily routines) and structure (e.g., social norms, sociopolitical, economic) on decision-making (Oshana, 2006). Rather than treatment decision conversations shaped from a perspective of individual autonomy and regulatory adherence (e.g., annual comprehensive patient assessments), the integrated care provider, patient, and DP should consider treatment decisions relationally and therefore engage in ongoing dialogue with the goal of the mutual understanding of experience, motivations, needs, and conditions (Phillips, 2007; Sledge et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…13879, 2019). Understanding shared decision-making activities between patient and decision partner (DP) dyads balances HCP accountability to payor and government standards with professional ethical responsibilities (Sledge et al, 2022).…”
mentioning
confidence: 99%
“…For people with kidney disease, discussion of treatment options and preferences through shared decision-making is recommended 1 year in advance of needing kidney replacement 2 8. Shared decision-making gives patients the opportunities to deliberate and carefully weigh the advantages and disadvantages of each individual treatment, using the best available evidence and educational programmes while being supported by healthcare professionals 9–11…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary search was conducted of MED-LINE, JBI Evidence Synthesis, the Cochrane Database of Systematic Reviews, and PROSPERO. The search revealed one published scoping review, 18 one scoping review protocol, 19 one systematic review, 20 one systematic realist review, 1 and five protocols of ongoing systematic reviews [21][22][23][24][25] with a similar topic to this scoping review. However, these studies differ from the proposed scoping review with regard to design, study population, major outcomes, or other study aspects:…”
Section: Introductionmentioning
confidence: 99%
“…1 The five protocols of ongoing systematic reviews identified in the preliminary search were registered in PROSPERO from 2017 to 2020. [21][22][23][24][25] The protocol by Sledge 21 aims to investigate shared decisionmaking and relational autonomy rather than investigating available patient involvement interventions. The protocol by Patel 22 aims to describe barriers and facilitators of ACP strategies and palliative care services for patients with organ failure in general, rather than specifically ESKD.…”
Section: Introductionmentioning
confidence: 99%